Exegetical journeys in biblical Greek: 90 days of guided reading - Merkle, Benjamin L. (Baker Academic, 2023)
A noted language expert provides 90 days of guided reading to help current and former students retain their knowledge and skill in reading and interpreting Biblical Greek.